Development of Learning Media Based Augmented Reality Electromagnetic Induction Subject Matter - Novie Amalia Izza Iksani; Nadi Suprapto (Indonesia Approach Education, 2022)
Learning about electromagnetic induction in physics calls for a deeper comprehension of abstract ideas and ways of thinking. This article is part of a development research project on augmented reality-based learning materials focused on electromagnetic induction. Its goal is to assess the reliability and efficacy of augmented reality-based learning materials with a particular emphasis on the cognitive learning outcomes of students. The 4-D development model